HEALTHCARE WASTE MANAGEMENT OF THE GOVERNMENT HOSPITALS IN NORTHERN PHILIPPINES - Charlie P. Cruz; Rosario C. Garcia; Paolo C. Colet; Jonas P. Cruz; Jerold C. Alcantara (European Scientific Journal, ESJ, 2014)
A validated Manual on Healthcare Waste Management (HCWM) for Level 1 Government Hospitals in Northern Philippines was developed based on the (1) profile of the (a) healthcare facility as to services, bed capacity, bed occupancy, and number of outpatients, and (b) medical staff as to HCWM training, awareness, vaccination, and staff contingent; (2) status of HCWM practices among respondents as to HCWM generation, segregation and handling, storage containers, storage areas, collection and on-site transport, off-site transport, treatment, final disposal, regulations, policy and budget, and sanitation and wastewater; and (3) the SWOT analysis of the HCWM implementation. Descriptive research design was employed on the current status of HCWM among 22 respondent hospitals as the identified cases. Standardized questionnaires adapted from the UN–WHO HCWM Rapid Assessment Tool were used and a survey based on observation and key informant interviews were the tools for data collection. Profile results indicate level 1 government hospitals responding to their functions of delivering quality services to their clients but staff profile were generally insufficient in terms of trainings responsive to proper implementation of HCWM. As to HCWM practices, there was awareness of HCWM requirements and diligent effort to comply, but HCWM efforts from waste generation, segregation and handling, storage containers, storage areas, collection and on-site transport, off-site transport, treatment and disposal were hampered by the usual problems in public facilities such as lack of logistics and funding and lack of training on HCWM and dissemination of rules and regulations, and inadequate provision of policy and budget. In conclusion, the Manual was deemed appropriate, helpful, and acceptable as a general guide for HCWM initiatives and hence is recommended for adoption.